Manusia dan Kebebasan dalam Pandangan Taqi Misbah Yazdi: Studi Kritis Terhadap Jean Paul Sartre - Firmansyah, Beta; Triandi, Dikdik; Hamdani, Basrir; Fahmi, Zulkifli Reza (Aqlania, 2023)
This research explores the views of Taqi Misbah Yazdi in criticizing the theory of human freedom according to Jean Paul Sarte. The discourse of human freedom has indeed been widely discussed, especially in modern times, especially in philosophy. Even in the West, this freedom is central to the discussion. The emergence of existentialism proves that the question of freedom has become a polemic among existentialist philosophers such as Soren Kierkegaard, Martin Haidegger, Karl Jasper and others. Researchers will focus on discussing Sartre's existentialism about human freedom. The method for this research is qualitative because this research is descriptive in nature and tends to use analysis. Process and meaning (subject perspective) are emphasized in qualitative research. The theoretical base is used as a guide so that the research focus is in line with the facts in the field. In this research, in terms of the existence of values, all the freedom that Sartre does certainly has weaknesses, namely it leads to anxiety, whereas in essence Sartre's freedom begins with human awareness of "being" and then acts in a conscious "nothingness". In Yazdi's study, awareness in noting this will make man detached from divine will in value and spiritually, meaning that the understanding of an absolute being that is conscious with a temporary form like man cannot be understood and studied, because the feeling of not noting it blackens and empties oneself into something that in the end, man will never find his own essence.Keywords: Responsibility, Circle of Freedom, Fear, Facticity.